Hypoglycemic and lipidemia effects of Notholaena nivea, «Cuti-Cuti» - Castañeda, C. B. (2022)
We evaluated the acute oral toxicity and the metabolic effect on glycemia and lipidemia in mice, of the metanolic extract of Notholaena Nivea, "Cuti-Cuti" to 10%, in CYTED models. The effect on plasma glucose was evaluated in normoglycemic and hyperglycemic rats, compared with control groups which received physiological serum. Hyperglycemia was induced with Alloxan, administered by intraperitoneal route to the dose of 150 mg/kg of weight. We used 60 rats distributed in three groups (I, II and III), of 20 rats each one. All the animals were put under 24 hours fasting, previous to the beginning of the experiments. Group I was subdivided in two sub groups of 10 animals each one and received physiological serum or extract of Cuti-Cuti, to observe its effects on normal blood glucose. The second group received alloxan to the dose of 150mg/Kg of weight, by intraperitoneal route, to induce experimental hyperglycemia; the values of blood glucose and lipids were determined at 1, 2, 4 and 24 hours. The third group of rats received 150 mg/kg of alloxan by intraperitoneal route. When the blood glucose level was over 300 mg%, 10 of them received 250 mg/kg of Cuti-Cuti and the others 10 received physiological serum by oral route. Determination of glucose, total cholesterol, HDL and triglycerids in plasma was made in the biochemical Autoanalizador Vitalab Selectra 2.The DL 50 with superior and inferior limit of 95% was 13,009 and 9,470 mg/kg of weight with an average of 11,099 mg/kg of weight. We found that the Notholaena nivea, "Cuti-Cuti", administered by oral route to the dose of 250mg/kg showed a good hypoglicemiant effect against the hyperglicemia induced by Alloxan; additionally it also reduces the triglycerids and cholesterol values, increased by the alloxan. In the phytochemical screening of the extract we found: phenolics, flavonoids, tannins, alkaloids, leucoantocyanidines, among others. Besides we found Rutin and Quercetin confirmed by TLC, HPLC, IR y RMNHI and an active principle that we have denominated CH-2.